PENDAMPINGAN MITIGASI RISIKO EKONOMI KELOMPOK PETANI PORANG DI DESA MRAYAN KECAMATAN NGRAYUN PONOROGO - Imam Fauzan; Tutik Heriana; Suyani Suyani (Jurnal Pengabdian Kepada Masyarakat, 2022)
The people of Mrayan village, Ngrayun sub-district, are mostly farmers where the Ngrayun people have triumphed with their cloves, and for now and the previous few years they have been empowered with people's porang and pine resin. People began to pay attention to this plant after knowing the exorbitant price. Here Porang is often dubbed the Golden Earth of Ngrayun. The service team from Unmer Ponorogo is directly targeting risk mitigation because this has a big impact on the financial sustainability of porang farmers, the risk of loss if not handled properly can certainly have an impact on the economic life of the individual porang farmers. In this activity the team used the PAR (Participatory Action Research) method. In this case, the service team acts as a companion and facilitator who must understand the characteristics and needs of the community. On the other side of the beneficiaries, namely the community, there is encouragement from partners who add enthusiasm and a completely new thought for them is an injection of energy that makes them more confident, growing and progressing. The potential of the existing community with additional knowledge from the academic community to better keep up with the times with technological information that continues to develop, both regarding the porang plant or the science that supports the success of its business to become more advanced. You can also get additional information about other people's experiences, other regions as well as the development of porang plants nationally.